A Communicative - Functional Philosophy of Translation - Al, Dangin; Sutanto, Dian Natalia; Sudarmo, Lucia Tri Natalia; Dewi, Novita (Indonesian Journal of English Language Studies (IJELS), 2016)
The Philosophy of translation is excluded from the framework of translation studies. Nevertheless, it is actually essential for developing the theory and practice of translation aswell as solving both internal and external challenges toward the theory and practice oftranslation. Hence, this article proposes the inclusion of philosophy in the framework andoffers a communicative-functional paradigm as the philosophy of translating from Indonesianinto English and vice versa. This paradigm construes translation as interculturalcommunicative act directed by the target-side purpose. It is rooted ontologically as therecodification of matrix code into target code which results in what Ricoeur calls as theequivalence without identity, epistemologically with the employment of cluster concept andaxiologically by directing intercultural mediation with three ethical principles i.e. the primacyof purpose, the loyalty to people and the respecting difference. In Indonesia especially inYogyakarta, based on the interview conducted to professional translators in PÃ©MadInternational Translation, this paradigm has been internalized by Indonesian translatorswithout conscious reflection of the paradigm as the philosophical foundation of theirtranslation practices.Keywords: translation, philosophy, communicative-functional paradigm